IDENTIFICATION OF DECLINE SUPPORTING FACTORS FOREST AND LAND FIRES WITH AHP (ANALYTICAL HIERARCHY PROCESS) METHOD IN THE RIMBO PANJANG VILLAGE TAMBANG SUBDISTRICT KAMPAR REGENCY - Muhamad Ridho; M.Mardhiansyah; Nurul Qomar (Jurnal Ilmu Ilmu Kehutanan, 2018)
In 2015 a major fire occurred again, one of them in the Rimbo Panjang Village Tambang Subdistrict, Kampar Regency. Until the year 2016-2017, cases of forest and land fires in the Rimbo Panjang Village decreased drastically than the number of hotspots in the previous year. This proves that the existence of supporting factors in efforts to decrease the number of hotspots of forest and land fires that need to be known. The purpose of this research is to determine the main factors supporting the reduction of forest and land fires and to know the efforts made by related parties to reduce forest and land fires in Rimbo Panjang Village. The methods in this study using AHP (Analytical Hierarchy Process). The results of this research indicate that the factors supporting the decrease of forest and land fires at the criterion level are climatology (0.382) and technique (0.204). Furthermore, the main factors supporting the reduction of forest and land fires to the factor level are drilling well (0.295) and the presence and role of MPA ( 0.210). Efforts that have been made by related parties are drilling wells and canal blocking and coordination and cooperation by all parties in the control, monitoring and prevention of forest and land fires.